Cancer cure in selected Malay medical manuscripts - Mohammad, Mardhiah; Mohd Shafri, Mohd Affendi; Dzulqarnain, Masoad (2018)
The Malay Archipelago has produced many medical manuscripts reflecting and documenting the availability, accessibility, and effectiveness of the locally occuring natural products used in the treatment of diseases. This study aims to review the treatment of tumour and cancer in several Malay medical manuscripts namely Kitab Tib Terengganu MS 1998.400, Kitab Al Rahmah Fi Al-Tibb 54/LL/14/YPAH/2005, and Kitab Ilmu Tabib (Warisan Perubatan Melayu). Natural products such as plants, animal, and minerals that have potential properties in treating cancer were identified in several recipes involving the incorporation of individual or mixed parts of plants and non-plants substances. It was found that many of these substances are yet to be screened as potential anti-cancer drug candidates. It was also found that the Malays identified and classified tumour and cancer not only as barah or ketumbuhan as is generally known today but also using several other key terms. In conclusion, tumour and cancer are among old diseases that were recognised by the Malays and the Malay manuscripts still contain many possible anti-cancer therapies that can be brought out to the fore for use in contemporary society.